Design, synthesis, biological evaluation and molecular dynamics of some novel 3-phenylpyrazolo[1,5-a]pyrimidine-2,7(1H,4H)-dione based compounds as anti-tubercular agents - Chauhan M.; Prajapati C.; Mirza S.; Barot R.; Yadav R.; Barmade M.; Kakadiya D.; Vijayvargia R.; Haobam B.; Baidya A.T.K.; Kumar R.; Yadav M.R.; Murumkar P. (My University, 2025)
Decaprenylphosphoryl-β-d-ribose-2′-epimerase (DprE1) is a druggable target which is being exploited for the development of new anti-TB agents. In the present work, we report developing a pharmacophore model and performing virtual screening of Asinex database using the developed pharmacophore model to get eight hits as potential DprE1 inhibitors. The hits were used as leads to design new 3-phenylpyrazolo[1,5-a]pyrimidine-2,7(1H,4H)-dione based potential anti-TB agents. On the basis of the identified lead molecules, a total of 18 compounds were synthesized and evaluated for their anti-TB activity by using MABA. ADMET predictions for all the compounds revealed that these compounds have drug-like and lead-like properties. One of the final compounds was found to exhibit potent anti-TB activity against Mycobacterium bovis. Communicated by Ramaswamy H. Sarma. © 2023 Informa UK Limited, trading as Taylor & Francis Group.